COVID-19 and prison system in Brazil: chronicle of a declared pandemic - Duarte, Joana das Flores (Argumentum, 2021)
Since March of this year the Covid-19 theme has been addressed from various angles. However, what draws our attention is the low visibility given to the Brazilian prison system, and the situation faced by male and female inmates. This article aims to raise awareness of this issue. Based on data from the National Survey of Statistical Information of the Brazilian Penitentiary System and from the Prison System Monitoring and Inspection Group, the analysis shows that the global health crisis caused by Covid-19 has been deepened by structural problems in prisons, which has increased the number of cases and deaths across the country.